Unsteady swirl distortion in a short intake under crosswind conditions - Piovesan, Tommaso; Zachos, Pavlos K.; MacManus, David G.; Sheaf, Christopher T. (American Institute of Aeronautics and Astronautics (AIAA), 2024)
In crosswind operating conditions, an aero-engine intake can be affected by notable unsteady flow distortions at the fan face. These distortions are typically associated with the ingestion of the ground vortex as well as with flow separation within the intake and can have a detrimental effect on the intake performance and therefore on the operability of the downstream compression system. Measurements of the unsteady velocity field within a model-scale intake under crosswind conditions were conducted using Stereo Particle Image Velocimetry (S-PIV) to characterize the velocity field and hence the intake flow distortion across the Aerodynamic Interface Plane (AIP) inside the duct. The intake distortion metrics were calculated for three operating conditions at a fixed crosswind velocity and increasing Mass Flow Capture Ratio (MFCR). The conditions at which the flow separates depend on crosswind velocity, ground clearance, the design of the intake and the MFCR. Flow characteristics of both low MFCR diffusion-driven, and high MFCR shock-induced separation were identified. The circumferential extent and intensity of the swirl distortion were found to be highly dependent on the crosswind velocity and MFCR. The swirl distortion caused by the diffusion-driven separation is greater than that due to shock-induced separation. The diffusion-driven separation was found to affect a bigger position of the intake AIP with higher time-average and peak values. An intermittent separation, that was observed for one value of MFCR in the range investigated, was found to cause peak levels of distortion twice the time-averaged values. Localized high swirl levels at a radial position near the intake surface correspondent to the tip region of a notional fan were observed. These can be expected to be detrimental to the operating stability of the downstream compression system.